Indigenous women entrepreneurship: analysis of a promising research theme at the intersection of indigenous entrepreneurship and women entrepreneurship. Issue 6 (2nd May 2020) - Croce, Francesca
ABSTRACT: This conceptual paper presents an international overview of Indigenous women entrepreneurship and consequentially develops the indigenous-gendered integrated perspective applied to the analysis of this emerging and promising research theme. Within the analytical tools of intersectionality and positionality, the complexity of IWE is outlined as well as the intersections discussed. The paper explores how the intersection of Indigenous entrepreneurship and Women entrepreneurship can contribute to the understanding of IWE and what theoretical and practical implications this can have.